2011
DOI: 10.1007/s00405-011-1582-2
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of cisplatin ototoxicity in rats by oral administration of pomegranate extract

Abstract: The aim of this study was to investigate the effectiveness of the oral administration of pomegranate extract (PE) as a protective agent against cisplatin-induced ototoxicity. The study included a prospective, controlled animal study Group 1 (n = 6), received no cisplatin or PE, and group 2 (n = 6) received cisplatin at 8 mg/kg/day for 3 consecutive days. Group 3 (n = 6) received not only cisplatin at 8 mg/kg/day for 3 consecutive days, but also received PE (100 μL/day) via gavage for 5 days prior to the cispla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 32 publications
2
17
0
1
Order By: Relevance
“…Some natural antioxidants, such as Vitamin E, Gingko Biloba, pomegranate and resveratrol (Yazici et al 2012;Olgun et al 2014), block the ototoxic effect of cisplatin. The otoprotective effect of resveratrol was observed only in low doses; otherwise, it enhanced the ototoxic impact of cisplatin in higher doses (Olgun et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Some natural antioxidants, such as Vitamin E, Gingko Biloba, pomegranate and resveratrol (Yazici et al 2012;Olgun et al 2014), block the ototoxic effect of cisplatin. The otoprotective effect of resveratrol was observed only in low doses; otherwise, it enhanced the ototoxic impact of cisplatin in higher doses (Olgun et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Entretanto, o CE 50 da cisplatina (55,87 ±1,10µM) é 4 vezes menor que o CE 50 da morina (220,30 ±1,08µM), sendo portanto, mais ativa (Tabela 01). Pesquisas mostram que a morina possui baixa toxicidade ao organismo, contrapondo-se a cisplatina que apresenta resultados limitados pelos efeitos colaterais como náusea, vômitos e nefrotoxicidade (Yazici et al, 2012;Said & Tsimberidou, 2014). Para o extrato de oliveira, não foi possível calcular o CE 50 por não atingir o limiar de 50%, apresentando efeito na dose de 800 µg/mL para o método de MTT (Figura 02).…”
Section: Determinação Da Viabilidade Da Célula H460 Tratada Com O Comunclassified
“…A previous study indicated that oral PPE decreases the levels of ROS, as well as acute inflammation in the tympanic membrane following myringotomy (11). Moreover, the oral administration of PPE in rats has been shown to reduce cisplatin-induced toxicity in the cochlea; therefore, an oral experimental dose of PPE may have a powerful effect in protecting cisplatin-induced ototoxicity in rats (12). However, the molecular mechanisms underlying PPE-induced protection from ototoxic drugs are not yet fully understood.…”
Section: Introductionmentioning
confidence: 99%